Recent Advances of SnO2-Based Sensors for Detecting Fault Characteristic Gases Extracted From Power Transformer Oil - Zhang, Qingyan; Zhou, Qu; Lu, Zhaorui; Wei, Zhijie; Xu, Lingna; Gui, Yingang (Frontiers in Chemistry, 2018)
Tin oxide SnO2 based gas sensors have been widely used for detecting typical fault characteristic gases extracted from power transformer oil, namely H2, CO, CH4, C2H2, C2H4, C2H6 and CO2, due to the remarkable advantages of good sensitivity, fast response, long-term stability, and so on. Herein, we present an overview of the recent significant improvement of high performance modified SnO2-based sensors in fabrication and application for detecting these fault characteristic gases. Promising materials for sensitive and selective detection of each fault characteristic gas have been identified. Meanwhile, the corresponding sensing mechanisms of SnO2-based gas sensors towards these fault characteristic gases are comprehensively discussed. In the final section of this review, the major challenges and promising developments in this domain are also given.